2014
DOI: 10.1155/2014/829469
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Toxicity Secondary toAsclepias physocarpa: The Balloon Plant

Abstract: We report a case of a 65-year-old woman with symptoms of blurred vision and ocular irritation a few hours after accidental contact of the right eye with Asclepias physocarpa milky latex. Observation showed a diffuse conjunctival hyperemia and stromal corneal edema with Descemet's membrane folds. Recovery was fast and apparently complete in less than one month. However, specular microscopy at 6-months follow-up showed an abnormal endothelial morphology as sequelae, suggesting this condition is not as innocuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…In our patient, we used aggressive anti-inflammatory treatment including topical prednisolone acetate 1% and cyclosporine 0.1% as well as oral prednisolone. Although previous reports suggest that the corneal endothelial toxicity associated with cardenolides can resolve spontaneously, 1 , 2 and addition of topical steroid would be enough,1, 2, 3, 4 , 8 all the patients in the cases were elderly of 60 year or older. The young age of our patient could be associated with an increased risk of more aggressive inflammation and tissue destruction, while the patient was healthy enough to tolerate vigorous topical and systemic anti-inflammatory treatment.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In our patient, we used aggressive anti-inflammatory treatment including topical prednisolone acetate 1% and cyclosporine 0.1% as well as oral prednisolone. Although previous reports suggest that the corneal endothelial toxicity associated with cardenolides can resolve spontaneously, 1 , 2 and addition of topical steroid would be enough,1, 2, 3, 4 , 8 all the patients in the cases were elderly of 60 year or older. The young age of our patient could be associated with an increased risk of more aggressive inflammation and tissue destruction, while the patient was healthy enough to tolerate vigorous topical and systemic anti-inflammatory treatment.…”
Section: Discussionmentioning
confidence: 82%
“…In a case of Asclepias fruticosa exposure in a 73-year-old male farmer, marked improvement was observed at day 3 after the use of 0.1% topical dexamethasone, and corneal edema completely resolved at 2 weeks 1 . Almost complete recovery was also obtained after using topical dexamethasone, ofloxacin and artificial tears in a case of Asclepias physocarpa exposure in a 76 year-old female patient, 8 although there was a possibility of endothelial distress, such as, pleomorphism and polymegathism, as a sequelae at 6 months 8 . Mikkelsen et al 4 used topical chloramphenicol 0.5%, dexamethasone 0.1% and scopolamine 0.2% in a 70-year-old male patient who was exposed to Asclepias tuberosa, and reported that the corneal edema resolved after 96 hours 4 .…”
Section: Discussionmentioning
confidence: 90%
“…The plants of the Asclepias genus are widely distributed as horticultural or ornamental plants in Japan and other countries, and latex from their stems has been shown to contain toxic components termed cardenolides. To our knowledge, only a few cases of cardiolides toxicity have been previously reported [13], and general ophthalmologists are unaware of these plants. In corneal endothelial cells, the Na + /K + ATPase actively transports Na + from inside of the cells into the anterior chamber to create an osmotic pressure gradient; thereby resulting in the active transport of water from inside the corneal stroma to the anterior chamber.…”
Section: Discussionmentioning
confidence: 99%
“…The use of topical steroids may increase the activity of the Na + /K + pump in corneal endothelial cells [5] and thus have utility in the treatment of plant-induced corneal edema. Therefore, we modelled our treatment on the approach reported by Pina et al [1], with the patient almost completely recovering within 6 days. Our patient fully recovered without any sequelae including any damage to corneal endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation